Impact of logging on a mangrove swamp in South Mexico: Cost/benefit analysis - Tovilla-Hernández, Cristian; Espino de la Lanza, Guadalupe; Orihuela-Belmonte, D Edith (Revista de Biología Tropical, 2001)
Environmental changes caused by logging in a mangrove swamp were studied in Barra de Tecoanapa, Guerrero, Mexico. Original forest included Rhizophora mangle, Laguncularia racemosa, Avicennia germinans and halophytic vegetation, and produced wood (164.03 m3/ha) and organic matter (3.9 g/m2/day). A total of 3.5 tons of wood per year were harvested from this area. Later, an average of 2 555 kg of maize per planting cycle were obtained (market value of 88 USD). Succession when the area was abandoned included strictly facultative and glycophyte halophytes (16 families, Cyperaceae and Poaceae were the best represented). After logging, temperatures increased 13ºC in the soil and 11ºC in the air, whereas salinity reached 52 psu in the dry season. These modified soil color and sand content increased from 42.6 to 63.4%. Logging was deleterious to species, habitat, biogeochemical and biological cycles, organic matter production, seeds, young plants, genetic exchange conservation of soil and its fertility, coastal protection, and aesthetic value; 3 000 m2 had eroded as the river advanced towards the deforested area (the cost/benefit analysis showed a ratio of 246: 1). There was long-term economic loss for the community and only 30% of the site has recovered after five years.